Canopy Microclimate Modification with Reflective Mulches Under Oil Palm and Its Role to Soybean Growth - Hidayat, Taufan; Koesmaryono, Yonny; Impron, Impron; Ghulamahdi, Munif (Agromet, 2020)
Land utilization under oil palm plantation is constrained by the condition of low light intensities. Modification of the microclimate through the use of reflective mulch, as a reflector, will increase its ability to reflect the land surface radiation under the tree stand. This modification may suitable for intercropping system between soybean and oil palm. The study aimed to determine the effect of microclimate modification, using reflective mulch, under the stand of oil palm, and to evaluate its effect on soybean productivity. The research was conducted at PTPN-VIII Cimarga Banten using a nested random design with two factors and three replications each. The first factor is the oil palm age, which consists of: (i) control (open land), (ii) 4 years, (iii) 5 years, and (iv) 8 years age of oil palm. The second factor is the reflective mulch, as a solar radiation reflector, which consists of three levels: (i) without mulch (control), (ii) inorganic reflective mulch/silver black plastic mulch, and (iii) organic reflective mulch/dried oil palm leaves. The application of inorganic and organic reflective mulch increased the distribution of reflected land surface radiation (59%-157%), reduced the soil temperature fluctuation (0.30C-1.20C), and maintained soil water content (45.2%-45.8%). An increased of plant growth rates (56%-86%), relative growth rates (16%-21%), and seed weight production per plant (74.8%-86.2%) also reported, as well as the reduction of the etiolation ratio (9.6%-12.5%). The use of organic and inorganic reflective mulches can improve the microclimate and increase the production of soybean under intercopping system with oil palm.